Training shortens search times in children with visual impairment accompanied by nystagmus - Huurneman, Bianca; Boonstra, F. Nienke (Frontiers in Psychology, 2014)
Perceptual learning (PL) can improve near visual acuity in 4-9 year old children with visual impairment. However, the mechanisms underlying improved near visual acuity are unknown. The present study compares feature search and oculomotor measures in 4-9 year old children with visual impairment accompanied by nystagmus (VI+nys [n=33]) and children with normal vision (NV [n=29]). Children in the VI+nys group were divided into three training groups: an experimental PL group, a control PL group, and a magnifier group. They were seen before (baseline) and after six weeks of training. Children with NV were only seen at baseline. The feature search task entailed finding a target E among distractor E’s (pointing right) with element spacing varied in four steps: 0.04°, 0.5°, 1°, and 2°. At baseline, children with VI+nys showed longer search times, shorter fixation durations, and larger saccade amplitudes than children with NV. After training, all training groups showed shorter search times. Only the experimental PL group showed prolonged fixation duration after training at 0.5° and 2° spacing, p’s respectively .033 and .021. Prolonged fixation duration was associated with reduced crowding and improved crowded near visual acuity. One of the mechanisms underlying improved crowded near visual acuity after PL in children with VI+nys seems to be prolonged fixation duration.